Spinal spatial integration of nociception and its functional role assessed via the nociceptive withdrawal reflex and psychophysical measures in healthy humans - Mauricio Carlos Henrich; Ken Steffen Frahm; Ole Kæseler Andersen (Physiological Reports)
Abstract Animal studies have previously shown that deep dorsal horn neurons play a role in the processing of spatial characteristics of nociceptive information in mammals. Human studies have supported the role of the spinal neurons; however, the mechanisms involved, and its significance, remain to be clarified. The aim of this study was to investigate spatial aspects of the spinal integration of concurrent nociceptive electrical stimuli in healthy humans using the Nociceptive Withdrawal Reflex (NWR) as an objective indication of spinal nociceptive processing. Fifteen healthy volunteers participated in the study. Electrical stimuli were delivered, using five electrodes located across the sole of the foot in a mediolateral disposition, as a single or double simultaneous stimuli with varying Inter‐Electrode Distances (IEDs). The stimulation intensity was set at 1.5× NWR threshold (TA muscle). The size of the NWR was quantified in the 60–180 ms poststimulus window as a primary outcome measure. Psychophysical measures were secondary outcomes. Single stimulation elicited significantly smaller NWRs and perceived intensity than double stimulation (p < .01), suggesting the presence of spatial summation occurring within the spinal processing. During double stimulation, increasing the inter‐electrode distance produced significantly smaller NWR sizes (p < .05) but larger pain intensity ratings (p < .05). By the NWR, spatial summation was shown to affect the nociceptive processing within the spinal cord. The inhibited motor response obtained when simultaneously stimulating the medial and lateral side of the sole of the foot suggests the presence of an inhibitory mechanism with a functional, behaviorally oriented function.